Biomedical Evaluation of Lansium parasiticum Extract-Protected Silver Nanoparticles Against Haemonchus contortus, a Parasitic Worm - Goel, Vanshita; Kaur, Pawandeep; Singla, Lachhman Das; Choudhury, Diptiman (Frontiers in Molecular Biosciences, 2020)
Here we show the novel antihelminthic potential of Lansium parasiticum aqueous extract protected silver nanoparticles (LAgNPs) against albendazole-resistant gastrointestinal parasite Haemonchus contortus. LAgNPs showed LD50 values of 65.6 ± 32.8 nM (12 h), 139.6 ± 39.9 nM (12 h), 64.3 ± 8.5 nM (24 h) against adult male, female and L3 Larvae respectively. LAgNPs was also quite effective in inhibiting egg hatching with an IC50 value of 144.4 ± 3.1 nM at 48 h exposure. Exposure to LAgNPs generated oxidative stress and mediated physical damage in the worms' tissue. A sharp increase in ROS and NOS levels was prominent due to LAgNPs' exposure. In response to oxidative stress, a sharp increase of stress-responsive enzymes activity like catalase, superoxide dismutase, glutathione peroxidase activity along with the concentration of glutathione was observed in worm tissue indicated LAgNPs responsive alteration of metabolism. The results give rise to the opportunity for the development of alternative treatment for drug-resistant parasitic worms.